3.2.1. Synthesis, crystal and molecular structure of catena-(bis(µ1-oxalic acid)-µ3-hydrogen oxalate-di-aqua-sodium(I)). (Communications in Inorganic Synthesis, 2015)
The crystal and molecular structure of catena-(bis(µ- oxalic acid)-µ-hydrogen oxalate-di-aqua-sodium(I)) was detected by X-Ray analysis. The compound crystallizes in the triclinic space group P-1, with a(Å) 6.2378(12); b(Å) 7,1115(14); c(Å) 10.489(2); Î±(°) 94.65(3); Î²(°) 100.12(3); Î³(°) 97.78(3). The sodium cation in the title compound is eight coordinated and forms a square antiprism. It is surrounded by two molecules of oxalic acid, one hydrogen oxalate anion and one water molecule. Both oxalic acid and hydrogen oxalate anion act as polydentate bridging ligands. Centrosymmetric sodium cations are bounded by hydrogen oxalate anions through a system of H bonds involving the molecules of oxalic acid. In the lattice, the 3D structure stabilized by H bonds is formed.